Penghindar Rintangan dengan Deteksi Jarak Berbasis Arduino Uno - Edy Setiawan, Galih Anindita (Politeknik Negeri Madura, 2016)
Advances in technology encourages people to further develop knowledge and skills, especially in control applications. In the era of global competition in finding a job is very high where job seekers locally or from abroad will compete to fill the vacancies that exist in Indonesia, and it is possible we will not compete with job seekers from abroad if we do not seek to increase competence. For the Indonesian government insisted that graduates from secondary schools to graduates of vocational colleges are required to be able to plunge into the field to be able to directly handle the job. Of the things that the discussion of this article will give you the knowledge of how to create applications with the obstacle avoidance control Detection Distance-Based Arduino Uno. Application control made gives the results for testing servo motor error average of 4.7%, for testing ultrasonic sensor error an average of 11.1% and for testing the movement of the dc motor if there is an obstruction shows the error of 0%, of the control application is expected to provide insight fundamental basis of the automatic control system, and also an understanding and application of microcontroller and proximity sensor.